Quasi-two-dimensional superconductivity from dimerization of atomically ordered AuTe2Se4/3 cubes - J. G. Guo (Nature Portfolio, 2017)
Emergent phenomena often appear in crystals in the two-dimensional limit but are rare in bulky compounds. Here, Guo et al. report a quasi-two-dimensional superconductivity in a bulk material AuTe2Se4/3 at 2.85 K, potentially owing to a topological transition.